ANALISIS PENGARUH INVESTASI PMA, PMDN DAN TENAGA KERJA TERHADAP PDRB SEKTOR PERTANIAN DI PROVINSI KALIMANTAN BARAT TAHUN 2005-2014 - Bo1111108, Fortunata Tri Yanisa (Jurnal Pembangunan dan Pemerataan, 2017)
AbstractThis reaserch is entitled an analysis of foreign direct investment, domestic investment and Labor of the agricultural sector GDP in West Kalimantan Year 2005-2014. This research aims to examine and analyze how much influence on gains from realization of foreign investment, domestic investment and Labor in West Kalimantan for the improvement of agricultural sector GDP in West Kalimantan. It was a quanitative descriptive study using the panel data regression model, as well as R Square test, F-test and t-test to test the hypothesis of whether the investment value and labor had an influence on the agricultural sector GDP in West KalimantanThese results indicate that Foreign Direct Investment has a positive impact amounting to 1.520547 but insignificant and foreign, positive effect amounting to 1.018171 too insignificant while the labor force positive and significant effect of 3.329256 however jointly or simultaneously, foreign direct investment, domestic investment, and labor has positive effect and significant impact on the agricultural sector GDP in West Kalimantan with Fstatistik 43.15982 with Prob value of 0.0000 is less than 0.05. The coefficient of determination (R2) amounting to 0.899916, or 90 percent, the meaning that the ability of foreign investment, domestic investment and labor in identifies changes of PDRB agricultural sector is 90 percent, while the remaining 10 percent is explained by other factors not included in the model in an increase in the GDP of agricultural sector in West Kalimantan Province.Keywords: Foreign Direct Investment, Domestic Investment, Labor and